Temperature Driven Membrane Lipid Adaptation in Glacial Psychrophilic Bacteria - Hassan, Noor; Anesio, Alexandre M.; Rafiq, Muhammad; Holtvoeth, Jens; Bull, Ian; Haleem, Abdul; Shah, Aamer Ali; Hasan, Fariha (Frontiers in Microbiology, 2020)
Bacteria inhabiting non-polar glaciers are exposed to large variations in temperature, which significantly affects the fluidity of bacterial cell membranes. In order to maintain normal functions of the cell membranes, psychrophilic bacteria adapt by changing the composition of cell membrane fatty acids. However, information on the exact pattern of cell membrane adaptability in non-polar low-temperature habitats is scarce. In the present study, 42 bacterial strains were isolated from the Ghulmet, Ghulkin and Hopar glaciers of the Hunza Valley in the Karakoram Mountain Range, Pakistan and their cell membrane fatty acid distributions studied, using gas chromatography/mass spectrometry (GC-MS) for the analysis of fatty acid methyl esters (FAMEs) liberated by acid-catalyzed methanolysis. Furthermore, Gram-negative and Gram-positive groups were grown under different temperature settings (5, 15, 25 and 35 °C) in order to determine the effect of temperature on cell membrane (CM) fatty acid distribution. The analyses identified the major groups of cell membrane fatty acids (FA) as straight-chain monounsaturated fatty acids (n-MUFAs) and branched fatty acids (br-FAs), accounting for more than 70% of the fatty acids analysed. The distribution of br-FAs and n-FAs in bacterial cell membranes was significantly affected by temperature, with the level of br-FAs decreasing relative to n-FAs with increasing temperature. Notably, the production of polyunsaturated fatty acids (PUFAs) was only seen at lower temperatures. This study contributes to understanding, for the first time, the role of br-FAs in the maintenance of cell membrane fluidity of bacteria inhabiting non-polar habitats.